Refugees as Entrepreneurs? A Challenge to HDP Programmes - Nascimento, Daniela (2024)
Protracted refugee situations in territories of war or natural hazards challenge the logic of the humanitarian-development-peace (HDP) nexus that inspires liberal humanitarianism. The organised expression of that nexus is the so-called ‘integrated approach’ in which humanitarian aid, development aid and peacebuilding are intertwined in missions aimed at promoting a durable peace. The experiences of camps for Palestinian and Syrian refugees in Jordan and of South Sudanese and Congolese refugees in Uganda question some basic assumptions of the HDP programmes. In the last two decades, the policies adopted in these locations show a two-fold reconfiguration of the HDP liberal programme: first, the aim of containing humanitarian crises locally, in the peripheries, thereby preventing their adverse effects spreading to the core of the international system; second, a focus on refugees’ capacity to become more resilient and entrepreneurial in order to overcome their vulnerable condition. Overall, this so-called neoliberal approach to humanitarianism with its focus on containment and individual entrepreneurship-inspired resilience has moved away from its liberal configuration as part of a systemic reconfiguration of local social fabric.